A Conceptual Framework: A Systematic Literature Review on Educational Leadership and Management - Osias Kit T. Kilag; Ann Merychris G. Manguilimotan; Robert P. Jordan; Peter Albert F. Columna; Maria Fe A. Camaso; Jelien C. Maraño (European Science Publishing, 2023)
The research aimed to provide a comprehensive understanding of the various leadership styles, theories, and practices that have been studied and applied in the field of education. Through a systematic literature review, the study analyzed and synthesized the existing body of knowledge on educational leadership and management, with a focus on the key themes of transformational leadership, collaborative leadership, ethics and values, emotional intelligence, and organizational culture. The results of the study revealed that transformational leadership has been widely recognized as a crucial factor in creating a positive and effective learning environment. Collaborative leadership, which involves the participation and engagement of stakeholders in decision-making, was also found to be a significant aspect of successful educational leadership. Additionally, the study emphasized the importance of ethics and values in leadership, as well as the role of emotional intelligence in promoting effective communication and interpersonal relationships. Finally, the study underscored the impact of organizational culture on the overall effectiveness of leadership and management practices in education. Overall, the study concludes that educational leadership and management is a complex and multi-faceted field, requiring a comprehensive understanding of various leadership styles, theories, and practices. The findings of the study contribute to the ongoing discourse on educational leadership and management, and provide a useful reference for practitioners, researchers, and policy makers in the field.
Keywords: educational leadership, management, transformational leadership, systematic literature review.